Concept of crime and punishment under Islamic Law / Abdul Razak Ahmad - Ahmad, Abdul Razak (Faculty of Law, 1987)
Law in every society aims at the maintenance of social control. It is a system which is primarily established to protect the rights of individuals as well as of society. The legal system in every society has its own nature, character and scope. Similarly, Islam has its own legal system known as Fiqh. Islamic law is not purely legal, in the strict sense of the term; rather it embraces all the spheres of life i.e., ethics, religion, political and economic. It has its origin in the Divine Revelation that is, the Quran. The Revelation determined the norms and basic concepts of Islamic Law. It should be noted that there are certain basic differences between the purpose and scope of law in Islam and in the other legal systems. The scope of Quranic laws comprise rules of human conduct in all spheres of life, ensuring men's well-being in his ordinary life as well as in the Hereafter. The enforcerrent of Islamic laws as contained in the Quran is the duty of an Islamic State. The application of the individual's rules of moral conduct is governed by two important factors, namely the Muslim society's colletive responsibility to observe Islamic teachings, and the individual's relationship with his Creater; Allah as well as with society. Muslim society is obliged according to the Quran, to enforce the application of rules of moral behaviour as divine carrrandrrents. The Quran repeatedly appeals to human conscience to follow the teachings of the Revelation for its own welfare as well as for the well-being of fellow human beings. Thus, the Quran, by making the observance of the rules of the Syariah a matter of human conscience, has dignified the concept of law and the ethical values of its teachings, which constitute the noblest and most perfect basis of universal laws.